STRATEGI PENGEMBANGAN NILAI-NILAI TOLERANSI DALAM RELASI SOSIAL SUNNI-SYI’AH DI PERKAMPUNGAN CANDI DESA BANJARAN–JEPARA - Fathimatuz Zahra; Muhammad Ghufron (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2018)
Differences are part of dynamic phenomenon of human communities that interact with each other. Because, religion as a source of inspiration for the creation of ethics, justice and sosial life as its main mission. Sunni and Syi’ah as historial facts for muslim in Indonesia. Both mazhab that have contributed in the process of indigenization of Islamic Nusantara. Now, these both mazhab are often bumped in difference. Escalation of conflict between the two increased until burning occurs and expulsion of Syi’ah groups at some places such as Sampang, Madura. This research is portraits occur in the Sunni-Syi’ah social space at Candi village Banjaran, Jepara. Researching dynamic of two communities Sunni-Syi’ah social relation at the Banjaran Village is established in a harmonious interaction, mutual respect in difference, upholding the values of peace and humanity. The result of this research showed the description of the development tolerance of both parties maintain brotherhood ukhuwah Islamiyah, through intercommunity of civic networks cultivation mutual trust in the pattern of negotiation and cooperation patern. As well as develop the power of social capital, cultural capital and symbolic capital in some activities that involve each other.